Effects of structural changes in the dsdA-dsdC intergenic region on D-serine deaminase synthesis. - McFall, E (1991)
Single-base-pair changes well upstream of its transcription initiation site resulted in partially to fully constitutive expression of the D-serine deaminase structural gene, dsdA, independently of the cyclic AMP-cyclic AMP-binding protein complex and of the specific D-serine deaminase activator protein. These promoter mutations appear to define a consensus sequence that is repeated several times. Basal expression of dsdA+ was also strongly enhanced by subcloning on multicopy plasmids, by the DNA gyrase inhibitor novobiocin, and in dsdC(Con) mutants by increasing growth temperature. These results suggest that activation of dsdA+ expression by the dsdC-encoded protein involves distortion of promoter DNA. A dsdA translation start at bp -731 was verified by subcloning of dsdC+. Plasmid-specified activator at a high concentration interfered with chromosomal dsdC(Con) expression, and the interference was enhanced by deletion of most of the intergenic region from the plasmid. Even at a high concentration, however, plasmid-specified activator did not activate expression of chromosomal dsdA+, and in one case it was actually repressive. These results confirm the strong cis tropism of plasmid-specified dsdC-encoded protein and suggest that it is mediated by multiple sites in the dsdA-dsdC intergenic region.